Developing Ability to Collect Patterns Using Natural Material Media in Class IV Students - Mohammad Archi Maulyda; Muhammad Erfan (Universitas Majalengka, 2022)
This research is based on the results of observations and experiences of researchers, that cognitive ability in compiling patterns is still low. The use of natural material media will be more fun for children in compiling patterns, because natural material media are very interesting for children. Based on this background, the problems studied were formulated, namely: